Szkło naczyniowe z klasztoru oo. Dominikanów w Brześciu Kujawskim, województwo włocławskie - Andrzejewska, Aldona (Acta Universitatis Lodziensis. Folia Archaeologica, 1996)
The excavations of the post-Dominican complex et Brześć Kujawski have yielded 257 glass fragments from which 76 vessels have been partly reconstructed. They include 52 narrow-neckcd bottles, 15 bell-shaped beakers, 2 jugs, 2 glasses and 4 pharmaceutic ampoules. All vessels came from layers linked with demolition and building works carried out by the monks at the close of the 18th up to the thirties of the 19th century. On the basis of stratigraphical sequence, associated finds, typological characteristics and results of chemical analyses it has been possible to assign the vessels in question to the period from the close of the 18th to the first half of the 19th century. The analysis of the chemical composition of the glass indicates that most vessels were made of sodium-calcium-potassium-magnesium glass. The ratio of particular alcaline components points to the use of raw material derived from the ashes of halophytes and of continental plants as well. Potassium glass is commonly regarded as a characteristic product of our lands. As the occurrence of the bell-beakers is also confined to Polish sites it is justifiable to assume that sodium glass has been produced in Poland at least since the end of the 18th century. Sodium glass could be made from material derived from halophytes growing in the regions of inland salt oans. The same applies to the bottles made according to sodium-calcium- potassium-magnesium recipes. Since the number of analyses of glass composition, made for selected samples, is still inadequate, errors may creep into the findings. As an example we can quote here the results of the analysis of the Brześć beakers inconsistent with data known from literature. Forest glass-works were active over the whole northern and central Europe, and so they would also produce potassium glass obtaining alcaline raw material from the ashes of ferns. Potassium bottles were also produced in France, England and other countries of that zone. Findings оГ the studies on the composition and production not only of Polish but also of Europea glass should be tested.